Bounce - Friend, Natasha, 1972- (Scholastic Press, 2007)
Thirteen-year-old Evyn's world is turned upside-down when her father, widowed since she was a toddler, suddenly decides to marry a woman with six children, move with Ev and her older brother from Maine to Boston, and enroll her in private school.